Barriers to Small and Medium Entrepreneurship in Kazakhstan: Qualitative and Quantitative Observations - SMAGULOVA, Sholpan; SABIROVA, Rysty; YERNIYAZOVA, Zhanat; ADIETOVA, Yelmira; UTEPKALIEVA, Kansulu; DYUSEGALIEV, Mukhit; BISEMBIEVA, Zhanargul (Journal of Advanced Research in Law and Economics, 2019)
Small and medium entrepreneurship is one of the determinants of the innovation economy, as well as the most important strategic resource for national development. The assessment of the efficiency and activity of small and medium entrepreneurship is carried out in a variety of ways. One of the tools that allows to position business entities in the system of integral economic coordinates is survey and ranks. A survey conducted by Kazakhstan Ministry of Economy, and National Economic Research Institute was evaluated by using SPSS software package (Statistical Package for the Social Sciences) to examine the relative importance of different barriers that affect the growth and operational effectiveness of SMEs in the developing countries with transition economies like Kazakhstan. The SPSS analysis indicated that a lack of awareness about laws and programmes, a lack of easy access to financial resources, level of corruption in public administration institutions, and poor access to and the quality of human resources are found to be the most important barriers, which have reduced the development of entrepreneurship in Kazakhstan. The findings of this study will assist the policy makers in the economy to create an environment conducive to the growth and consistent outstanding performance of SMEs in any economy.